Role of government towards adoption of cleaner technologies for climate proactivity: A survey-based empirical study of Indian firms. Issue 1 (3rd January 2017) - Satapathy, Santanu Kumar; Sangle, Shirish; Unnikrishnan, Seema
Abstract : Purpose: There is a need for considerable attention on the adoption of cleaner technologies (CT) by firms for climate proactivity for developing countries such as India. Literature survey suggests that government, market and civil society are the key drivers of CT adoption (CTA) in developing countries. The purpose of this paper is to investigate the mediating and moderating role of the government in CTA for climate proactivity. Design/methodology/approach: The data collected from a survey of Indian firms were analyzed through exploratory factor analysis and multiple regression analysis to examine the mediating and moderating role of the government. Findings: The empirical outcome was compared with the current government policies to summarize the research findings. Research limitations/implications: There is scope of future research to examine the moderating and mediating role of market and civil society in CTA for climate proactivity. Practical implications: The study will provide significant insight into various stakeholders associated with the CTA such as government, technology manufacturers, marketing community, environmental professionals and associated researchers. The research model will be useful for policymakers, managers and researchers for understanding CTA in the Indian context. Social implications: The output model will be useful for the government to formulate forward-looking strategies toward the adoption of CT by industries for climate proactivity. Originality/value: Unlike previous studies in which the government was recognized as a key driver of CTA, this study makes an attempt to test the moderating/mediating role of government in CTA in India. The findings of the study are supported by adequate empirical evidence.